Reproducibility of three dimensional digital preoperative planning for the osteosynthesis of distal radius fractures. Issue 12 (2nd May 2017) - Yoshii, Yuichi; Kusakabe, Takuya; Akita, Kenichi; Tung, Wen Lin; Ishii, Tomoo
ABSTRACT: A three‐dimensional (3D) digital preoperative planning system for the osteosynthesis of distal radius fractures was developed for clinical practice. To assess the usefulness of the 3D planning for osteosynthesis, we evaluated the reproducibility of the reduction shapes and selected implants in the patients with distal radius fractures. Twenty wrists of 20 distal radius fracture patients who underwent osteosynthesis using volar locking plates were evaluated. The 3D preoperative planning was performed prior to each surgery. Four surgeons conducted the surgeries. The surgeons performed the reduction and the placement of the plate while comparing images between the preoperative plan and fluoroscopy. Preoperative planning and postoperative reductions were compared by measuring volar tilt and radial inclination of the 3D images. Intra‐class correlation coefficients (ICCs) of the volar tilt and radial inclination were evaluated. For the implant choices, the ICCs for the screw lengths between the preoperative plan and the actual choices were evaluated. The ICCs were 0.644 ( p  < 0.01) and 0.625 ( p  < 0.01) for the volar tilt and radial inclination in the 3D measurements, respectively. The planned size of plate was used in all of the patients. The ICC for the screw length between preoperative planning and actual choice was 0.860 ( p  < 0.01). Good reproducibility for the reduction shape and excellent reproducibility for the implant choices were achieved using 3D preoperative planning for distal radius fracture. Three‐dimensional digital planning was useful to visualize the reduction process and choose a proper implant for distal radius fractures. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2646–2651, 2017. Abstract : A three‐dimensional (3D) digital preoperative planning system for the osteosynthesis of distal radius fracture was developed for clinical practice. The reproducibility of the reduction shapes and selected implants using 3D planning in the patients with distal radius fractures were evaluated. Good reproducibility for the reduction shape and excellent reproducibility for the implant choices were achieved using 3D preoperative planning. Three‐dimensional digital planning was useful to visualize the reduction process and choose a proper implant for distal radius fractures.